Paraparesis in Hb D-Hb E Heterozygous Thalassemia- a Case Report - Ahammad, Faruk; Masud, Abu Ahmed Abdullah; Hassan, Riad (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Thalassemia is a group of autosomal recessive hemoglobinopathies where exramedullary hemopoisis is frequently observed in the liver, lymph nodes, spleen and also around spinal cord which may cause spinal cord compression producing different clinical manifestations including para paresis or paraplegia. A case report of thoracic spinal cord compression in a 20-year-old male with Hb D-Hb E heterozygous thalassemia is reported from medicine department of Bangabandhu Sheikh Mujib Medical College, Faridpur. Bangladesh. This patient presented with progressive weakness of both lower limbs and difficulties in walking for 2 months. He also had history of fluctuating jaundice since childhood. His hemoglobin electrophoresis was suggestive of Hb D-Hb E heterozygous and MRI of dorsal spine with screening whole spine reveals extramedullary hemopoiesis at D2 to D12 causing spinal cord compression and low signal intensity of the bone marrow of the vertebrae. After blood transfusion he underwent referred to higher specialized center (National Institute of Neurosciences and Hospital, Dhaka) for further better management. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):110-112